Hunter access affects elk resource selection in the Missouri breaks, Montana. Issue 7 (12th July 2016) - Proffitt, Kelly M.; Thompson, Scott; Henry, Drew; Jimenez, Benjamin; Gude, Justin A.
ABSTRACT: Elk ( Cervus canadensis ) populations that exceed socially tolerable population levels create problems with private landowners over property damage and competition with livestock. Increasing harvest of adult female elk is the primary management tool for curtailing elk population growth and reducing elk populations. However, this tool is not effective when elk are not accessible to hunters during hunting seasons. The purpose of this project was to evaluate the effects of hunter access and other landscape factors on second‐order and third‐order elk resource selection during the archery and rifle hunting seasons in 2 populations: the Missouri River Breaks (MRB) and Larb Hills, Montana, USA. In our resource selection models, we first treated the individual elk‐year as the sampling unit to estimate individual‐level selection coefficients and second, we pooled data from all individuals to estimate population‐level selection coefficients. Second‐order population‐level selection coefficients indicated that elk in MRB and Larb Hills selected home ranges in areas with no hunter access, and hunter access was the strongest predictor of second‐order selection. Similarly, third‐order population‐level selection coefficients indicated elk in both populations selected locations within their seasonal home range with no hunter access, and the strength of selection for locations with no hunter access was stronger in the archery season than the rifle season. However, individual models revealed that although third‐order population‐level selection for locations with no hunter access was strong, only 46% of elk in the MRB selected for no hunter access during the archery season and 24% of elk selected for no hunter access during the rifle season. Additionally, the majority of all elk locations in the MRB (i.e., 68% of archery locations, 91% of rifle locations) occurred in areas accessible to hunters. These results highlight that population‐level selection coefficients may not always represent individual selection patterns, and we recommend employing a combination of population‐level and individual animal models as the basis of developing biological inferences. Even if hunter access is restricted in a relatively small geographic area within an elk population range, those areas may have a disproportionate effect on elk distributions and prevent effective harvest of female elk to maintain populations at objective levels (i.e., 1, 700–2, 000 elk). Working cooperatively with stakeholders to minimize elk harboring is necessary for curtailing further elk population increases and maintaining a distribution of elk across public and private lands. © 2016 The Wildlife Society.